Redundant CArG Box Cis-motif Activity Mediates SHATTERPROOF2 Transcriptional Regulation during Arabidopsis thaliana Gynoecium Development - Sehra, Bhupinder; Franks, Robert G. (Frontiers in Plant Science, 2017)
In the Arabidopsis thaliana seed pod, pod shatter and seed dispersal properties are in part determined by the development of a longitudinally-orientated dehiscence zone that derives from cells of the gynoecial valve margin. Transcriptional regulation of the MADS protein encoding transcription factors genes SHATTERPROOF1 (SHP1) and SHATTERPROOF2 (SHP2) are critical for proper valve margin (VM) identity specification and later on for dehiscence zone (DZ) development. Current models of SHP1 and SHP2 regulation indicate that the transcription factors FRUITFULL (FUL) and REPLUMLESS (RPL) repress these SHP genes in the developing valve and replum domains, respectively. Thus the expression of the SHP genes is restricted to the VM. FUL encodes a MADS-box containing transcription factor that is predicted to act through CArG-box containing cis-regulatory motifs. Here we delimit functional modules within the SHP2 cis-regulatory region and examine the functional importance of CArG box motifs within these regulatory regions. We have characterized a 2.2kb region upstream of the SHP2 translation start site that drives early and late medial domain expression in the gynoecium, as well as expression within the VM and DZ. We identified two separable, independent cis-regulatory modules, a 1kb promoter region and a 700bp enhancer region, that are capable of giving valve margin and dehiscence zone expression. Our results argue for multiple independent cis-regulatory modules that support SHP2 expression during VM development and may contribute to the robustness of SHP2 expression in this tissue. Additionally, three closely positioned CArG box motifs located in the SHP2 upstream regulatory region were mutated in the context of the 2.2kb reporter construct. Mutating simultaneously all three CArG boxes caused a moderate de-repression of the SHP2 reporter that was detected within the valve domain, suggesting that these CArG boxes are involved in SHP2 repression in the valve.